Cryptic intronic transcriptional initiation generates efficient endogenous mRNA templates for C9orf72-associated RAN translation - Shannon L. Miller; Katelyn M. Green; Bradley Crone; Jessica A. Switzenberg; Elizabeth M. H. Tank; Amy Krans; Karen Jansen-West; Clare M. Wieland; Eric W. Ji; Leonard Petrucelli; Sami J. Barmada; Alan P. Boyle; et al. (Proceedings of the National Academy of Sciences, 2025)
Intronic GGGGCC hexanucleotide repeat expansions in C9orf72 are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Despite its intronic location, this repeat avidly supports synthesis of pathogenic dipeptide repeat (DPR) proteins via repeat-associated non-AUG (RAN) translation. However, the template RNA species that undergoes RAN translation endogenously remains unclear. Using long-read based 5′ RNA ligase-mediated rapid amplification of cDNA ends (5′ Repeat-RLM-RACE), we identified C9orf72 transcripts initiating within intron 1 in a C9BAC mouse model, patient-derived iNeurons, and iNeuron-derived polysomes. These cryptic m 7 G-capped mRNAs are at least partially polyadenylated and are more abundant than transcripts derived from intron retention or circular intron lariats. In RAN translation reporter assays, intronic template transcripts–even those with short (32 nucleotide) leaders–exhibited robust expression compared to exon–intron and repeat-containing lariat reporters. To assess endogenous repeat-containing lariat RNA contributions to RAN translation, we enhanced endogenous lariat stability by knocking down the lariat debranching enzyme Dbr1. However, this modulation did not impact DPR production in patient-derived iNeurons. These findings identify cryptic, linear, m 7 G-capped intron-initiating C9orf72 mRNAs as an endogenous template for RAN translation and DPR production, with implications for disease pathogenesis and therapeutic development.